Bridging the Gap: making Nepal’s health insurance financially sustainable - Sanjel, Seshananda; Kafle, Bharat (Journal of Karnali Academy of Health Sciences, 2026)
Sustainable health financing is essential for building a resilient health system that ensures equitable access to quality healthcare without financial hardship. In Nepal, the Government introduced the National Health Insurance Program (NHIP) in 2017 under the Health Insurance Act as a major step toward achieving Universal Health Coverage (UHC). However, the country faces significant challenges due to demographic and epidemiological transitions, including population aging, rising non-communicable diseases, and persistent infectious diseases, which increase healthcare demand and costs. Public health expenditure remains below 2% of GDP, far below the recommended benchmark for UHC, while heavy reliance on out-of-pocket payments and low NHIP enrollment, particularly among informal-sector workers, weaken financial protection. Additional barriers include fragmented financing schemes, weak governance, inefficient budget allocation, and dependence on declining donor support. The National Health Financing Strategy (2080–2090) aims to address these gaps by expanding fiscal space, increasing domestic resource mobilization, reducing out-of-pocket expenditure, and strengthening risk pooling. Progressive taxation, sin taxes, public–private partnerships, strategic purchasing, and improved governance are critical reforms. A comprehensive, evidence-based financing approach is necessary for Nepal to achieve equitable, efficient, and sustainable UHC